Beyond the ontological turn: affirming the relative autonomy of politics - Khan, Gulshan Ara (SAGE Publications, 2017)
In this article, I critically evaluate a characteristic tendency that is found across the various traditions of poststructuralism, both narrowly and more broadly defined. This is an increasing propensity to be preoccupied with ontological questions and seemingly at the expense of either a refinement of political concepts or a concrete analysis of forms of power and domination. I consider the reasons for this development and stress how this characteristic feature of poststructuralism appears to follow from the very fact of ontological pluralism. What we see in contemporary continental thought is a proliferation of different traditions, and each side seeks to defend their position in ontological terms. Following this, I advance the idea of a relative autonomy between ontology and politics, where the former does not determine the latter in any direct or straightforward fashion. I argue that we need to stress this relative autonomy to open a little space between ontology and politics, space where we can return poststructuralism to a more concrete engagement with ‘the political’.